Diary of travels and adventures in Upper India (vol.I): from Bareilly, in Rohilcund, to Hurdwar, and Nahun, in the Himmalaya Mountains, with a tour in Bundelcund, a sporting excursion in the Kingdom of Oude, and a voyage down the Ganges - Davidson, C J C (Munshiram Manoharlal Publishers, 2004)
Description and travel of the author in India in 1840s.